Good governance in rural development : country specif issues and experiences, proceedings of the COMSEC-BARD organized International Training Course on Good Governance in Rural Development 20 April - 02 May 2008 - Kashem, Mohammed Mir; Karim, Abdul; Parvin Irin (Bangladesh Academy for Rural Development, 2007)
Chiefly with reference to South Asia.